2019
DOI: 10.1007/s12311-019-01080-y
|View full text |Cite
|
Sign up to set email alerts
|

Alanyl-tRNA Synthetase 2 (AARS2)-Related Ataxia Without Leukoencephalopathy

Abstract: Mutations in the mitochondrial alanyl-tRNA synthetase gene, AARS2, have been reported to cause leukoencephalopathy associated with early ovarian failure, a clinical presentation described as "ovarioleukodystrophy". We present a sibling pair: one with cerebellar ataxia and one with vision loss and cognitive impairment in addition to ataxia. Neither shows evidence of leukoencephalopathy on MRI imaging. Exome sequencing revealed that both siblings are compound heterozygous for AARS2 variants (p.Phe131del and p.Il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…In the previous 3 cases without leukoencephalopathy, cerebellar atrophy was constant, the disease course was progressive, and 2 of them had cognitive decline. 6,7 It is also worth noting that downbeat nystagmus, which is caused by impairment of flocculus and paraflocculus, was constantly found in the patients without leukoencephalopathy. In addition, tremor, usually of an action type, appears to be frequently associated with AARS2 mutations.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the previous 3 cases without leukoencephalopathy, cerebellar atrophy was constant, the disease course was progressive, and 2 of them had cognitive decline. 6,7 It is also worth noting that downbeat nystagmus, which is caused by impairment of flocculus and paraflocculus, was constantly found in the patients without leukoencephalopathy. In addition, tremor, usually of an action type, appears to be frequently associated with AARS2 mutations.…”
Section: Discussionmentioning
confidence: 98%
“…5 Recently, 3 patients have been reported with infantile/adult onset of progressive ataxia, pyramidal signs, and cognitive decline, in whom brain MRI showed cerebellar atrophy without leukoencephalopathy. 6,7 We report the clinical and genetic characteristics of 2 sisters with slight and nonprogressive ataxia, downbeat nystagmus, action tremor, normal cognition, and primary amenorrhea, who harbored two novel mutations in AARS2. Brain MRI was unremarkable, not showing leukoencephalopathy or cerebellar atrophy.…”
mentioning
confidence: 99%
“…In another article Lakshmannan et al point out white matter rarefaction as a distinctive feature of AARS2 -L compared to HDSL/ALSP, which is not observed in our patient. On the other hand, recent case reports [ 9 , 10 ] show that AARS2 mutations not always give rise to leukodystrophy at all, and previous reports have shown cases with very few, and asymmetric white matter changes [ 6 , 22 ]. Thus the group of leukodystrophies, even narrowed within a single gene mutation, is heterogeneous, and from a neuroradiological point of view, the process of diagnosing adult leukodystrophies will require a systematic approach [ [25] , [26] , [27] ] and supplementation by next generation genetic sequencing diagnostics.…”
Section: Discussionmentioning
confidence: 99%
“…There are various symptoms and their prevalence differ among patients. Cases with ataxia, demyelinating polyneuropathy and tremor, basal ganglia and cerebellar symptoms as well as a case with progressive optic neuropathy have also been described [ [9] , [10] , [11] ]. There is currently no treatment for the condition.…”
Section: Introductionmentioning
confidence: 99%
“…A similar complementation assays approach was recently used to assess the impact of new mutations in AARS2 identified in patients presenting ataxia without leukoencephalopathy. The yeast results showed that the F102del mutation in ALA1 (human F131del) led to loss of function, whereas the ala1 V306M (human I328M) is a hypomorphic allele [ 29 ]. It must be underlined that the approach used in these studies suffers the limit that the effects on cytoplasmic aminoacylation and on cytoplasmic protein synthesis rather than the effects on their mitochondrial counterparts are mainly evaluated, resulting in potentially flawed results.…”
Section: Functional Studies Of Mt Ars Genes Mutations In Yeastmentioning
confidence: 99%